Distribution Pattern of Gafrarium tumidum and Their Habitat Conditions in Mangrove Ecosystems of Rutong Village and Waai Village, Ambon Island - Janson Hans Pietersz; Imanuel Villian Trayanta Soukotta; Elizabeth Miklen Palinnussa; Yofita Anaktototy (Masyarakat Moluska Indonesia, 2024)
Gafrarium tumidum species on Ambon Island can be found in the mangrove ecosystem areas of Rutong Country and Waai Country, when sea water conditions recede the people of Rutong Country and Waai Country often use G. tumidum species for consumption. The purpose of this study is to determine the density and distribution pattern of G. tumidum, know the habitat conditions and know the relationship between the abundance of G. tumidum and its habitat characteristics. The process of collecting data on mangrove conditions, Gafrarium tumidum species and environmental parameters was carried out using the Stratified Random Sampling method. Data collection of mangrove canopy cover was carried out using a simple Hemispherical Photography method. The highest density of G. tumidum is found in Waai Country with a distribution pattern of G. tumidum in Rutong Country has a uniform distribution pattern and in Waai Country has a clustered distribution pattern. The habitat conditions of G. tumidum can be explained that, only Sonneratia alba species found at all observation stations in both locations with overall mangrove conditions in both locations having sparse density conditions and moderate canopy cover. Salinity conditions at both locations vary. Then the substrate condition in both locations there are two types of substrate, namely sandy stone and rocky sand with the most dominant type of substrate in both locations, namely sandy stone. The relationship between the abundance of G. tumidum and habitat characteristics in each location has an inverse or negatively correlated relationship and the abundance of G. tumidum is more likely to cluster at Rutong 1 and Waai 5 stations.